Proposed conservation of the name Gastrimargus Saussure, 1884 (Orthoptera: Acrididae: Oedipodinae) threatened by an unused senior homonym - Heads, Sam W.; Maehr, Michael D. (Zootaxa, 2009)
Gastrimargus Saussure, 1884 includes 23 species of economically important locustine grasshoppers (Acrididae: Oedipodinae: Locustini) distributed throughout Africa, Australia and Southeast Asia (Ritchie, 1982). Whilst reviewing oedipodine genus-group names in the Orthoptera Species File Online (Eades & Otte, 2009) we encountered an unused senior homonym—Gastrimargus Spix, 1823 used for a genus of Neotropical primates —which has seniority over Gastrimargus Saussure, 1884 according to the Principle of Priority (ICZN, 1999: Article 23.1). However, the senior homonym is universally considered as a junior synonym of another genus and has not been used as valid since 1899, thereby qualifying as a nomen oblitum. Here we present a case for the ‘automatic’ conservation of Gastrimargus Saussure, 1884 following the requirements of Article 23.9.2 of the Code.